Hubungan Tingkat Pengetahuan Terhadap Perilaku Swamedikasi Penyakit Scabies di Pondok Pesantren Modern X Kabupaten - Mailatul Ilal Haq; Like Efriani; Idmanurrahman Hadi (Universitas Borneo Lestari, 2023)
Scabies is a skin disease that is often overlooked (neglected disease). Scabies disease is still common and the prevalence rate is still high in Islamic boarding schools. Self-medication is carried out to treat mild to moderate illnesses without doctor's advice. Good self-medication requires good knowledge too. This research was conducted to determine the relationship between the level of knowledge and the self-medication behavior of scabies at Modern X Islamic Boarding School, Cirebon Regency. This study uses an observational method with a cross-sectional approach, the sampling technique uses random sampling. The research instrument was a questionnaire on the level of knowledge and self-medication behavior that had been tested for validity and reliability. The results showed that the level of self-medication knowledge of students was in the good category with a percentage of 52% (41 people) and the self-medication behavior for scabies was also included in the good category with a percentage of 76% (75 people). There is a relationship between the level of knowledge of scabies self-medication behavior with a correlation value of 0.701 and a significance of 0.00.